El auge del cristianismo en el imperio romano (Estudio Agustiniano, 2008)
Few recent publications by sociologists on Early Christianity have aroused such a great commotion among the scholars as the book authored by Rodney Stark. For sure, issues regarding the Roman Empire's conversion to Christianity have been long a matter of controversy for historians and theologians. However, Stark’s sociological model heats up the debate by providing provocative, insightful and stimulating proposals which this article examines in depth.